Advancements in integrating MOFs into micro-arc oxidation coatings on Mg alloys: A perspective on PEO-MOF coatings as innovative corrosion inhibitors - A.G. Ramu; Daejeong Yang; Minjung Song; Dongjin Choi (Journal of Magnesium and Alloys)
The favorable properties of Mg alloys, such as their lightweight and robust nature, are driving an increase in interest in their development for industrial and biomedical applications. These benefits aren't enough to make them widely used; problems like poor corrosion resistance and no antibacterial qualities call attention to the need for improved coating methods. Because of its distinct characteristics and efficacy in surface modification, plasma electrolytic oxidation (PEO) has emerged as a preferred coating process. But protective coatings can only become better with time if we keep pushing them to new limits. PEO coatings on Mg alloys may be made more protective by using metal-organic frameworks (MOFs). Hybrid crystalline MOFs have been popular in inorganic and organic chemistry in recent decades. These complexes include organic ligands and metal ions or clusters. Large specific surface areas, customizable topologies and functionalities, ordered pore structures, and many reactive sites make these materials famous. Preventing corrosion using MOFs seems promising. This study analyzes MOF-led corrosion protection material advances and their efficacy in tackling corrosion challenges. A comprehensive review of numerous production techniques employed with MOFs for corrosion protection highlights their pros and cons. The report also discusses MOFs' potential corrosion-prevention functions and the challenges that must be overcome to make them viable. The corrosion-preventive ways of MOFs as inhibitors, nano-fillers, nano-containers, and surface-coating agents are also examined. As we conclude our detailed analysis, we provide a future-oriented vision of MOFs' undiscovered corrosion prevention potential. This exposition illustrates corrosion protection material advances employing cutting-edge MOF-based anticorrosion breakthroughs. It encourages creative ways to corrosion protection's future.